Pengaruh Susunan Hybrid Serat Resam Dan Ijuk Pada Matriks Polyester Untuk Mengetahui Nilai Impak - Roperiadi; Napitupulu, Robert; Juanda, Juanda (Jurnal Inovasi Teknologi Terapan, 2023)
Along with the times, synthetic composite materials are often used as materials for making reinforcing car panels, car dashboards and other interior devices. Although synthetic composite materials have strong strength, synthetic composite materials are less environmentally friendly and have an expensive price. Natural fibres are an alternative to synthetic fibres in order to reduce natural pollution and reduce production costs. Therefore, in this research I will use palm fibre and resam as reinforcement material. The purpose of this research is to find out whether mixing between resam fibre and palm fibre to make a car dashboard has reached the standardised value of making a car dashboard. The hand lay-up method will be combined with the Taguchi method in the L9(34) orthogonal matrix design used as a guide for making test specimens. With tensile and impact testing. This study used variations in volume fraction of 25%, 30%, 35% fibre, as well as variations in fibre length of 30mm, 40mm, 50mm with 2h NaOH immersion. The highest average value of impact test strength was at 30% volume fraction of fibre with 30mm fibre length with a value of 0.0617 Joule and the lowest average value was at 25% volume fraction of fibre with 50mm fibre length with a value of 0.0307 Joule.